Indonesia's Marine Economic Potential As A Maritime Country: Marine Economy - Hastuti, Hastuti; Muhidu, Amiruddin; Rastin, Rastin; Agus Mokodompit, Eliyanti (Publisher Cv. Inara, 2023)
This nation has economic potential that is no less flashy and dazzling in terms of natural resources and the environment. The main purpose of this article is to emphasise the importance of Indonesia's marine economic potential as a maritime country in achieving Indonesia's prosperity and glory as a maritime country. Fisheries, marine tourism, marine transportation, offshore energy and mineral resources, marine industry, marine buildings, and marine services are all goals for the marine economic spectrum. This marine resource's potential economic value is estimated to be at least 8.22 trillion per year. This article was written using qualitative and descriptive literature studies. A literature review was used as the research method to analyse the journal. Reviewing related libraries is what a literature review entails. (Review of related literature/review of literature) The findings indicate that the Indonesian government already has a policy in place for Indonesia's marine strategy, which refers to Indonesia's Development Vision, which is contained in Law Number 17 of 2007 concerning the National Long-Term Development Plan 2005-2025 and Law Number 32 of 2014 concerning Marine. This policy is reflected in a number of concepts, including Blue Economy, Maritime Domain Awareness, World Maritime Axis, and Nusantara Insight. To realise Indonesia as an independent, advanced, and strong archipelagic country based on national interests, this great potential must be managed and utilised holistically, integrated thematically, and distributed spatially proportionally through an integrated development planning process supported by harmonious spatial planning and the implementation of sustainable development that can run in harmony.